PENGATURAN ADVOKASI TERHADAP HAK-HAK PENYANDANG DISABILITAS TERHADAP DISKRIMINASI DI BIDANG PENEGAKAN HUKUM - Sutrisni, Ni Komang (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 1 (2015), 2015)
Human Rights is the rights of human beings are naturally without exception and a privilege for the group, as well as the level of a particular social group. These rights are freedom  speech with freedom from all forms of oppression that must be upheld, not only by each individual of a State that recognizes the existence and respect of Human Rights itself, but must also be guaranteed by countries without any exceptions, including persons with disabilities in dealing with legal issues. This study use d normative research for examining the principles and rules of law by using the legislation approach, and case-based approach . The regulation is regarding human rights in general stipulated in the Constitution Republif of Indonesia 1945, Act 39 of 1999 on Human Rights, Law No. 4 of 1997 on Persons with Disabilities, Law 19 of 2011 on the Ratification of Convention on the Rights of persons with Disabilities, International Covenant on Civil and Political Rights (ICCPR). The right to non-discriminatory treatment as a continuation of the right to equal treatment before the law for persons with disabilities can be realized through the exercise of the right to a fair trial. All such regulations prohibit all forms of discrimination and guarantee to all persons equal and will be effective protection against discrimination on any basis .
Keywords: Advokacion; persons with disabilities; discrimination; law enforcement